Biometrical data of adult Brasiolis sophorae L. (Lep. Brassolidae), in Fortaleza, Ceará, Brazil - Bastos, José Alberto Magalhães (Pesquisa Agropecuaria Brasileira, 2014)
This paper deals with the study of Brassolis saphorae L., measurement. In the various adult specimens of B. sophorae L., the following determination has been accomplished: longitude/width ratio (of front and hind wings) and breadth of the wings. It was not seen a good concordance between front wings longitude and breadth of the wings. The longitude/width ratio has had small variation.